Population-based virucidal phthalocyanine gargling/rinsing protocol to reduce the risk of coronavirus disease-2019: a community trial - Brito-Reia, Verônica Caroline; da Silva Bastos, Roosevelt; Vieira Vilhena, Fabiano; Marques Honório, Heitor; Marques da Costa Alves, Lucas; Frazão, Paulo; Sérgio da Silva Santos, Paulo (German Medical Science GMS Publishing House, 2022)
Aim: In this community trial, the objective was to evaluate the incidence of coronavirus disease-2019 (COVID-19) cases in two similar communities in three distinct phases: 1 (before the intervention), 2 (during the intervention), and 3 (after the intervention). Methods: The test community received the oral antiseptic intervention (experimental), while the control community did not. The official information agency ("Statewise System for Data Analysis") provided the number of confirmed COVID-19 cases. Data were analyzed according to the three phases per epidemiological week (epi) using the R Core Team (2021) program. The relative risk and 95% confidence intervals between the cumulative incidence values of the test and control communities were calculated for each period. In the test community, a total of 995 residents over 10 years of age received two bottles containing 600 ml of mouthwash containing antiviral phthalocyanine derivative (APD). The participants were asked to gargle/rinse with of 5 mL of the mouthwash containing ADP 3 to 5 times a day, for 1 min, until the bottles were empty. Results: In phases 1 and 3, the disease risk between the two communities did not differ significantly (p>0.05), while in phase 2, the disease risk was 54% lower in the test community than in the control community. Conclusion: The use of the APD mouthwash protocol seems to reduce the COVID-19 incidence at the population level, and further studies are needed to confirm its protective effect under more precisely controlled conditions.